2000
DOI: 10.1161/01.cir.102.14.1611
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Troponin I Level on Admission Is Associated With Adverse Outcome of Primary Angioplasty in Acute Myocardial Infarction

Abstract: In patients with ST-segment elevation AMI, an elevated cTnI on admission is associated with an increased risk of primary angioplasty failure and a more complicated clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 25 publications
9
54
2
1
Order By: Relevance
“…[1][2][3][4][5][6] However, data on troponin's effects on actual clinical care compared to CK testing alone in a heterogeneous patient population (including patients with and without acute cardiac disease presenting at different times in their illnesses with and without classic symptoms and diagnostic ECGs) are limited. In one such population, we found that combined CK and troponin I (CKTnI) testing led to more ED discharges than CK testing alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] However, data on troponin's effects on actual clinical care compared to CK testing alone in a heterogeneous patient population (including patients with and without acute cardiac disease presenting at different times in their illnesses with and without classic symptoms and diagnostic ECGs) are limited. In one such population, we found that combined CK and troponin I (CKTnI) testing led to more ED discharges than CK testing alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, troponin testing has been shown to be especially useful for stratifying patients into those who could benefit from interventions such as low-molecular weight heparin and GPIIa/IIIb inhibitors. [4][5][6][7] These were not widely available or used at the study hospital during the majority of this study, and it is possible that in settings where these are standard interventions, troponin could be shown to influence clinical care and outcomes in different or additional ways. Discharge diagnoses were made based on all clinical information available to the study's inpatient physicians and were not independently verified.…”
mentioning
confidence: 99%
“…She did not have any evidence of cardiac dysrhythmias during her stay in the emergency room. Initial Troponin I (normal <0.4 ng/mL) and CK-MB (normal <7.7 ng/mL) were elevated at 7.82 ng/mL and 55.2 ng/mL, respectively [7,8]. Six hours later, Troponin I increased to 13.44 ng/mL and CK-MB to 75.7 ng/mL.…”
Section: Casementioning
confidence: 99%
“…Because of its prolonged release in the blood, these biomarkers are useful diagnosing sub-acute myocardial infarction [4]. Studies showed that patients with elevated admission cTnI had a significantly higher incidence of cardiac mortality and of cardiac events, i.e., death, nonfatal myocardial infarction, target-vessel revascularization [6]. …”
Section: Troponin I (Tni)mentioning
confidence: 99%